2004
DOI: 10.1161/01.cir.0000143832.91812.60
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Coronary Artery Disease Associated With Polymorphism of the Cytochrome P450 Epoxygenase CYP2J2

Abstract: Background-Cytochrome P450 (CYP) 2J2 is expressed in the vascular endothelium and metabolizes arachidonic acid to biologically active epoxyeicosatrienoic acids (EETs). The EETs are potent endogenous vasodilators and inhibitors of vascular inflammation. However, it is not known whether genetic polymorphisms of CYP2J2 are associated with increased cardiovascular risks. Methods and Results-All 9 exons of the CYP2J2 gene and its proximal promoter were sequenced in 132 patients to identify potential variants. Funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
214
3
5

Year Published

2006
2006
2012
2012

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 231 publications
(230 citation statements)
references
References 14 publications
8
214
3
5
Order By: Relevance
“…There is little known about the importance of this endogenous system within the heart even though the heart contains significant levels of functionally active CYP. Finally, and most importantly, recent human epidemiological evidence has identified associations between CYP2J2 polymorphisms and CAD, and EPHX2 polymorphisms and CHD [43,45,46,84]. These findings provide strong evidence supporting the notion that EETs play an important role in postischemic functional recovery and perhaps infarct size reduction [31,33,36,83].…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…There is little known about the importance of this endogenous system within the heart even though the heart contains significant levels of functionally active CYP. Finally, and most importantly, recent human epidemiological evidence has identified associations between CYP2J2 polymorphisms and CAD, and EPHX2 polymorphisms and CHD [43,45,46,84]. These findings provide strong evidence supporting the notion that EETs play an important role in postischemic functional recovery and perhaps infarct size reduction [31,33,36,83].…”
Section: Resultssupporting
confidence: 61%
“…These studies highlight the complexity of the CYP enzyme system, emphasize the role of different CYP metabolites in cardioprotection and suggest caution in the interpretation of results when using non-selective CYP inhibitors. Recent epidemiologic data suggests an association between single nucleotide polymorphisms in the genes encoding CYP2J2, CYP2C8, CYP2C9 and EPHX2 and cardiovascular disease risk in humans supporting the functional relevance of the CYP epoxygenase pathway in the heart [43][44][45][46][47].…”
Section: Arachidonic Acid Cyp Epoxygenases and Soluble Epoxide Hydromentioning
confidence: 93%
“…All DNA samples were genotyped for 25 SNPs of 18 XME genes by PCR-restriction fragment length polymorphism (RFLP) assays according to the array protocols available from the publications. [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] Supplementary Table 3 shows SNPs that have been analyzed in the study. PCR was performed in a final volume equal to 25 ml of reaction mixture containing 1.5 U of thermostable Taq DNA polymerase (Lytech, Moscow, Russia), B1 mg DNA, 0.25mM of each primer, 250 mM of dNTPs, 1.5-3.5 mM of MgCl 2 and 1Â PCR buffer (67 mM Tris-HCl pH 8.8, 16.6 mM (NH 4 ) 2 SO 4 , 0.01% Tween-20).…”
Section: Genotypingmentioning
confidence: 99%
“…Some EETs-derived metabolites play important roles in the regulation of vascular tone [15,16]. Moreover, it has been shown that CYP2J2-derived metabolites are involved in the recovery of heart function following ischemia in mice [17], that the risk of coronary artery disease is associated with polymorphisms in CYP2J2 gene in humans [18], and that CYP2J2-derived products are involved in cardiac electrophysiology [19,20]. EETs and EETs-derived metabolites are also involved in a host of processes related to cancer cell behavior, angiogenesis and tumor pathogenesis [21,22].…”
Section: Introductionmentioning
confidence: 99%